Pengaruh Pendapatan, Literasi Keuangan, dan FOMO terhadap Perilaku Konsumtif Mahasiswa Pengguna Shopee dalam Perspektif Islam - Fahrezi, Mochamad Zaky; Balqis, Siti Rania; Rahmawati, Deliana; Azzahra, Aulira Mahel Putri (Jurnal Bintang Pendidikan Indonesia, 2024)
This study aims to analyze the influence of income, financial literacy, and Fear of Missing Out (FOMO) on the consumptive behavior of students who use Shopee from an Islamic perspective. The research employs a quantitative approach with data collected through questionnaires distributed to Shopee-using students, utilizing a Likert scale of 1–5. The sampling technique applied is accidental sampling, and data analysis is facilitated by SPSS software. The results reveal that the Adjusted R Square value of 13% indicates that income, financial literacy, and FOMO explain 13% of the variance in students’ consumptive behavior, while the remaining 87% is influenced by other factors not included in the study. Simultaneous testing shows an F-value of 5.420 with a significance of 0.002, confirming that the three independent variables significantly affect students’ consumptive behavior. Notably, financial literacy and FOMO have significant impacts on students’ levels of consumption. This study contributes to the literature on consumptive behavior in the context of Islamic values and provides practical guidance for students to manage their consumption wisely. Additionally, the findings offer valuable insights for e-commerce platforms to design more responsible marketing strategies aligned with Islamic principles.